Molecular docking and admet studies of 3-phenyl coumarin derivatives for their Antiâ€cancer activity - SIMPI MEHTA; SUMIT; NANCY GOYAL; SEEMA R.PATHAK (International Journal of Pharma and Bio Sciences, 2016)
Cancer is one of the most prevalent diseases worldwide. Research community is untirely working on prevention and control of this disease by targeting various enzymes and proteins via synthetic and natural products. In the present study novel 3-phenyl coumarin derivatives were designed. All the compounds of this series were subjected to molecular docking studies for inhibition of 5 different proteins. The molecular docking study results revealed that, all the designed ligands showed binding energy (ranging from -13.4 to -44.0) and docking score (ranging from -3.27 to -9.56). ADME-Toxicity prediction reported that all novel coumarin derivatives were in the acceptable range of various pharmacological parameters. Total seven novel ligands were studied on 10 pdb ID’s of five different proteins. Out of seven ligands five ligands i.e. 3, 4, 5, 6 and 7 have shown excellent docking score ranging from -9.56 to -8.21 on two proteins i.e. Amine Oxidase and Protein kinase. All these five ligands showed good affinity than reference compound capecitabin and R-(-) –deprenyl. These in silico results can thus serve as a template for further invitro and invivo studies to have novel drug for cancer with minimum toxicity.